Diagnostic Management of Oncogenic HPV Cervical Infections: The Field Experience in Wuxi, China - Liu, Yang; Yin, Yongxiang; Zhang, Yi; Lin, Luling; Zhao, Min; Chen, Qi (Frontiers in Medicine, 2022)
Introduction: A liquid-based cytology test was introduced for cervical cancer screening in the 2000s worldwide. However, the concordance of diagnostic findings between the liquid-based cytology test and cervical biopsy has not been fully investigated, especially the overall failure rate on the diagnosis in cervical cancer and high-grade squamous intraepithelial lesion (HSIL) by cytology test. The aim of this retrospective study was to investigate the concordance between ThinPrep cytology and histology test in the diagnosis of cervical cancer and HSIL in HPV-positive women. Methods: ThinPrep cytology test was performed in 2,472 HPV-positive women. Of them, the cervical biopsy was concurrently performed in 1,533 women. Data on the HPV type and the diagnostic findings of the ThinPrep cytology test and cervical biopsy were collected from our hospital electronic database. The concordance of diagnostic findings between histology and cytology was compared. Results: The rate of agreement in the diagnosis of the low-grade squamous intraepithelial lesion (LSIL) or HSIL between cervical biopsy and ThinPrep cytology test was 58% or 49%. The overall false-negative rate in the diagnosis of cervical cancer and HSIL by ThinPrep cytology test was 6%. However, when considering the total number of women diagnosed with cervical cancer and HSIL by cervical biopsy, we found that a significant number of HPV-positive women with cervical cancer (n=12, 33%), or women with HSIL (n=77, 66%) were failed to be diagnosed by the ThinPrep cytology test. These HPV-positive women were either diagnosed with cervical infection or ASCUS, or LSIL. Discussion: Our data demonstrated that in order to ensure an accurate diagnosis, an immediate cervical biopsy in women with cervical infection or ASCUS or LSIL should be strongly recommended in clinical practice.